Pemahaman Konseptual Keselamatan dan Kesehatan Kerja (K3): Tinjauan Sistematis terhadap Penyebab dan Pencegahan Kecelakaan Kerja - Sukma Ayu Raganingtyas; Tanto Prima; Mardiyah Mardiyah (Jurnal Mahasiswa Manajemen dan Akuntansi, 2025)
Occupational Health and Safety (OHS) is a strategic instrument in creating a safe, healthy, and productive work environment, as well as a determining factor for organizational sustainability. This article aims to comprehensively examine the concept of OHS by highlighting the causes of workplace accidents, the associated risk factors, and the prevention strategies that can be applied across various sectors. The research method employed a systematic literature review with a mapping review approach, drawing on books and indexed scientific publications. The collected data were analyzed using content analysis and narrative synthesis techniques to provide a comprehensive overview of OHS issues.The findings reveal that workplace accidents generally occur due to the complex interaction between human factors, environmental conditions, and management systems. Basic factors such as fatigue, mental pressure, and limited knowledge create vulnerabilities that increase the likelihood of accidents. These conditions are further aggravated by unsafe acts and unsafe conditions, which are often overlooked or insufficiently addressed. Effective prevention strategies require synergy between individuals and organizations through continuous training, the cultivation of a safety culture, consistent supervision, and the proper use of personal protective equipment. Furthermore, managerial commitment to integrating OHS into organizational policies has been shown to contribute significantly to reducing workplace accidents and enhancing productivity.Thus, OHS should not only be regarded as a normative obligation but also as a strategic investment that protects workers, improves quality of life, and strengthens organizational competitiveness in the context of modern industrial dynamics.